The analysis of powers of the state authorities in the control of public procurement - Горбатюк, Яна Вадимівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In the article the concept of the control in public procurement and the state authorities, which according to the law, it is carried out, are defined, powers of control in the field of public procurement and some problems of its implementation are analyzed. One of the aspects of the implementation of economic policy in our country are issues of public procurement. The functioning of public procurement requires ensuring effective use of public funds for the development of competition, transparency and openness of the procurement process. Since the existence of any system is impossible without the creation of adequate conditions of control of its functioning, the issue of state control over the implementation of public procurement procedures is quite relevant. The control of public procurement in modern conditions plays an important role, dues to the large number of violations and abuses in public procurement. Since control in public procurement is carried out by public authorities, it refers to one type of state control. The Law of Ukraine "On public procurement" has made numerous changes to the procedure of public procurement. The control of public procurement is a systematic monitoring of spending of public funds in the acquisition of goods and services of good quality, in the right amounts, at the right time, at an affordable price, in a suitable supplier for public funds to ensure fair competition among participants, openness and transparency at all stages of procurement, as well as objective and impartial evaluation of bids. One of the main tasks of the Antimonopoly Committee of Ukraine is participation in the formation and implementation of competition policy control to create a competitive environment and the protection of competition in public procurement. Nowadays some problems related to the using of updated legislation arise in the area of public procurement, particularly in the area of state regulation and control of public procurement. The Law of Ukraine "On public procurement" clearly defines a comprehensive list of public authorities, which can control in public procurement such as the Antimonopoly Committee of Ukraine, the Accounting Chamber, the State Audit Office of Ukraine to be distinguished from the bodies exercising state regulation of public procurement. Despite the constant updating of the legislation on public procurement, so far there are problems with the implementation of state control of public procurement.